Effects of Pollution on Fish Behavior, Personality, and Cognition: Some Research Perspectives - Jacquin, Lisa; Petitjean, Quentin; Côte, Jessica; Laffaille, Pascal; Jean, Séverine (Frontiers in Ecology and Evolution, 2020)
Pollutants, and more generally, environmental stressors, are a neglected source of behavioral and cognitive variations in wild populations. Based on recent literature in fish, we highlight four interesting research perspectives to better understand the effects of pollutants on the links between behavior, cognition and fitness. First, (1) we review the neurotoxic effects of pollutants on fish behavior, personality and cognition. These effects could in turn affect the level of exposure to pollutants, potentially generating feedback loops that may amplify the effects of pollutants on fitness. Second, we propose that (2) the effects of pollutants should be studied in a multistress context, i.e. in realistic environmental conditions in combination with other stressors, because some stressors could amplify the behavioral effects of pollutants on fitness. Third (3), existing studies show that physiological and behavioral traits are often linked in syndromes. Pollutants could lead to syndrome disruption, which could affect the evolutionary trajectories of exposed populations. Future studies should thus focus on the complex links between traits to better understand the consequences of stressors on evolutionary trajectories. Fourth, (4) exposure to chronic pollution could lead to local (mal)adaptation, which could result into high intraspecific variability of sensitivity among populations. In addition, evolutionary responses to pollution could constrain, or be constrained by evolutionary responses to other stressors. We thus encourage future studies to use integrative approaches to bridge the gap between ecotoxicology, cognitive ecology and evolutionary ecology in a multistress framework to improve our ability to predict the effects of anthropogenic stressors on wildlife.